A multi-scale method for predicting the properties of 3D braided composite under three-point bending load - Guoqing Yu; Boqiang Shi; Yanhua Shen (Materials Research Express, 2021)
A more versatile and efficient multi-scale coupling finite element method for researching the mechanical response of 3D braided composites under three-point bending load is represented in this paper. In the mesoscale, the multiphase representative unit-cell models are established to describe the mesoscopic structure which consists of braiding yarns and matrix. In the macroscale, the unit-cells are regarded as homogeneous material, and the load and constraint conditions are applied on the macroscopic structure model. The multi-scale homogenization theory is introduced to calculate the equivalent stiffness matrixes of mesoscopic unit-cells and build the mathematical relationships between the mesoscopic stress fields and the macroscopic strain fields. According to the element damage criterion, the bending modulus and ultimate load-bearing ability of 3D braided composites are predicted by simulating the progressive damage process of unit-cells Comparing with the experimental result, the predicted result satisfies the required precision for engineering.